Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/0886022x.2019.1700804
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical risk factors and outcomes of massive ascites accumulation after discontinuation of peritoneal dialysis

Abstract: Background: Encapsulating peritoneal sclerosis (EPS) is a serious complication of peritoneal dialysis (PD), with high morbidity and mortality that requires an early diagnosis for effective treatment. PD withdrawal and bacterial peritonitis are important triggers for the onset of EPS. However, few studies have focused on cases of PD withdrawal without a clinical diagnosis of peritonitis, cirrhosis, or carcinomatosis. We aimed to compare the clinical characteristics and computed tomography (CT) images of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In a recent study, Chen et al demonstrated that patients with persistent ascites accumulation after PD withdrawal were at a high risk of progression to full-blown EPS. 11 It was suggested that the inflamed peritoneum was leading to large volume ascites accumulation. 12 In our case, the weekly amounts of ascites consistently increased despite oral steroid and tamoxifen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Chen et al demonstrated that patients with persistent ascites accumulation after PD withdrawal were at a high risk of progression to full-blown EPS. 11 It was suggested that the inflamed peritoneum was leading to large volume ascites accumulation. 12 In our case, the weekly amounts of ascites consistently increased despite oral steroid and tamoxifen therapy.…”
Section: Discussionmentioning
confidence: 99%